THE IMPACT OF BRAND TRUST, BRAND IMAGE AND EMOTIONAL BRANDING ON CUSTOMER SATISFACTION: STUDY ON IKEA FURNITURE INDUSTRY - Yesika Larasati; Muhammad Yani; Lilik Indayani; Alshaf Pebrianggara (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Brand Trust, Brand Image, and Emotional Branding on Customer Satisfaction in IKEA Indonesia customers. Method: This study uses a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis technique. Primary data was obtained through the distribution of questionnaires to 108 respondents who had purchased and used IKEA furniture products, using purposive sampling techniques. Results: The results of the study show that all independent variables, namely Brand Trust, Brand Image, and Emotional Branding, have a positive and significant effect on Customer Satisfaction. These findings indicate that trust in the brand, strong brand image perception, and emotional engagement of customers in the shopping experience have an important role in increasing customer satisfaction levels. In practical terms, this study provides implications for IKEA to strengthen its marketing strategy oriented towards emotional experience as well as consistency of product and service quality. Novelty: The value of this research's contribution lies in affirming the role of emotional aspects and brand perception in shaping customer satisfaction in the modern furniture industry.